(untitled) (Latakia University Journal -Basic Sciences Series, 2021)
Thirty samples of sands from Daakana site, northeast of the town of Al-Qaryatein, were studied and the grain size coefficients were determined in order to estimate the predominated environment during sedimentation processes (determining the mean energy and sedimentation conditions). The granular analyzer was used to analyze the sediment granular size and to study its distribution, GSSTAT (Grain Size Statistics Program) program was used to obtain the histological statistical parameters. The results showed the possibility of dividing the sand size into medium and finesized grain, and that it was deposited in a shallow marine environment that had been subjected to the influence of turbidimetric processes, which contributed to the sorting of grains and the absence of organisms. transporteing by rolling process indicated the precipitation of sand deposits in marine environment. These deposits had lenses from in the lower areas as a result of withdrawal of the sea.